Dental Cavity Liners for Class I and Class II Resin-Based Composite Restorations - Khaled Mohammed Alharbi,; Majed Abdullah Almajed,; Salman Dhaifalla K Alanazi,; Husam Khalid Althaqeb,; Fawaz Saad Alfawaz,; Tariq Othman Alothman,; Khalid Ibrahim Alkhodair,; Abdullah Ibrahim Bin Jammaz,; Ahmed Murayh Alanazi,; Mohammed Abdulaziz Alateeq, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Dental cavity liners are commonly used in Class I and Class II RBC restorations to protect the pulp, promote healing, and improve restoration success. Aim: This meta-analysis study aimed to evaluate the comparative effectiveness of different dental cavity liners in Class I and Class II resin-based composite restorations, with a focus on their role in reducing post-operative hypersensitivity and preventing long-term restoration failure. Methods: A comprehensive investigation has been performed in databases involving PubMed, Embase, Cochrane Library, and Google Scholar, utilizing a combination of textual terms and medical subject headings related to dental cavity liners and postoperative hypersensitivity. Additional searches were performed on ClinicalTrials.gov, and references from selected investigations were reviewed to determine relevant observational research. Results: The meta-analysis discovered statistically insignificant differences between groups regarding postoperative hypersensitivity and restoration outcomes. Specifically, POH by patient report (Y/N) (Z = 1.60, P = 0.11), POH evaluated utilizing the visual analog scale (Z = 1.47, P = 0.14; mean difference: 0.39, 95% CI: 0.11 to 1.37), and POH measured by cold response (CRM) at 1-week (Z = 0.86, P = 0.39) and 1-month follow-ups (Z = 1.50, P = 0.13) all showed no significant differences. Restoration failure at 1-year follow-up also demonstrated no significant difference between groups (Z = 0.00, P = 1). Conclusion: This meta-analysis concluded that the use of dental cavity liners in Class I and Class II resin-based composite restorations did not significantly impact postoperative hypersensitivity or long-term restoration failure. These results suggest that modern adhesive systems may offer sufficient protection without the need for cavity liners. Future research should explore specific clinical contexts and newer liner materials to better inform restorative practices.